2011
DOI: 10.1371/journal.pone.0014492
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Regulation of Monocyte Inflammatory Response to an Intracellular Pathogen

Abstract: Systemic bacterial infections elicit inflammatory response that promotes acute or chronic complications such as sepsis, arthritis or atherosclerosis. Of interest, cells in circulation experience hydrodynamic shear forces, which have been shown to be a potent regulator of cellular function in the vasculature and play an important role in maintaining tissue homeostasis. In this study, we have examined the effect of shear forces due to blood flow in modulating the inflammatory response of cells to infection. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Since chemokine upregulation was concomitant with shear exposure, it is likely that this shear-induced enhancement is mediated at the translational level or released from existing stores. Together with our previous study, 16 this work underscores the importance of the interaction between biochemical and biomechanical stimuli in determining the inflammatory response.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Since chemokine upregulation was concomitant with shear exposure, it is likely that this shear-induced enhancement is mediated at the translational level or released from existing stores. Together with our previous study, 16 this work underscores the importance of the interaction between biochemical and biomechanical stimuli in determining the inflammatory response.…”
Section: Discussionsupporting
confidence: 80%
“…26,43 The cytokines from infected monocytes can activate the endothelium to recruit leukocytes from the blood. 16 The chemokine gradient triggers leukocyte migration into the plaque site, which is a critical step in inflammation. The increase in chemokine gradient due to infection and shear exposure correlates well with the increase in monocyte migration across the barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that infected macrophages form clusters, which are densely packed cells in certain areas of the 3D collagen matrix, thus supporting the cause of higher actin polymerization, spreading, and movement of infected cells ( Figure 5C ). This clustering may also be a result of aggregation due to the upregulation/activation of adhesion receptors, including integrin, and ICAM-1 in infected cells ( Evani et al, 2011 , 2013 ). Although macrophages infected with chlamydial antigen did not show clustering at the end of 1 week; at the end of 2 weeks, they also exhibited areas with significantly high cell density (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Although uncommon, severe sepsis caused by C. pneumoniae has previously been reported 1 . C. pneumoniae infection can alter monocyte morphology and trigger release of proinflammatory cytokines 2. Its role in the pathogenesis of atherosclerosis has been well studied; however, antibiotic treatment trials for secondary prevention of late stage coronary disease were negative 3…”
Section: Descriptionmentioning
confidence: 99%